S-METRIC SPACES FIXED POINT RESULTS ON ALTMAN INTEGRAL TYPE MAPPINGS - M.L.L.Phanikanth, T.Siva Krishna, M.Vijaya Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
In this present article, we establish the concept of